A prospective study of a urine and plasma biomarker test for the prediction of gleason ≥3 + 4 prostate cancer in a mixed cohort. (3rd July 2020) - Poulsen, Mads Hvid; Feddersen, Søren; Albitar, Maher; Poulsen, Charlotte Aaberg; Lund, Martin; Pedersen, Torben Brøchner; Mortensen, Mike Allan; Lund, Lars
Abstract: Purpose: Definitive diagnosis of prostate cancer is based on biopsies, a procedure associated with side-effects. The use of biomarkers in blood and urine could potentially help clinicians select patients for whom biopsies are needed. The aim of the study was to test a new urine and plasma biomarker test in detecting medium and high grade prostate cancer. Materials and methods: Blood and urine samples were prospectively collected from 41 patients prior to prostate biopsy or TUR-P and again after 3 months. The cohort included patients with suspicion of prostate cancer and patients with prior prostate cancer diagnosis. The mRNA expression of ten selected genes measured by PCR were used together with clinical data in multiple algorithms for prediction of medium-high grade prostate cancer in prostate biopsies. The testing was originally developed and validated in the USA. The method was transferred to a local Danish laboratory. Medium and high grade cancer was defined as Gleason score ≥ 3 + 4. Results: Using the biomarker test, prior to any prostate procedures, the sensitivity for detecting medium-high grade prostate cancer was 100% and the specificity was 56% and 63%, depending on the cut-off point used. When using the biomarker test, following biopsy or TUR-P, the sensitivity and specificity were reduced to 89% and 28–34% respectively. When comparing results, there was a significant difference ( p  < 0.05), favoring the test performed prior to the procedures. Conclusions: We were able to predict the presence of medium-high grade prostate cancer, thereby confirming earlier findings of the biomarker test.